Factors influencing pain intensity in knee osteoarthritis: a cross-sectional biopsychosocial perspective - Bayrak, Gökhan; Alkan, Halil (BioMed Central Ltd, 2025)
Background: Pain is pivotal in managing knee osteoarthritis (KOA), necessitating tailored rehabilitative strategies. The biopsychosocial framework suggests that a multifaceted approach is crucial for understanding and managing pain in KOA patients. This study explored the factors that influence pain intensity through biological and psychosocial determinants from a biopsychological perspective in KOA patients. Methods: This cross-sectional study included 150 KOA patients with Kellgren-Lawrence (K/L) grades 2–4. Patients were classified into three groups based on their Visual Analogue Scale scores: mild (n = 79), moderate (n = 40), and severe pain intensity (n = 31). The biological determinants included the body mass index, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for knee function, the 30-second sit-to-stand (30STS) test for functional strength, and the Timed-Up and Go (TUG) test for mobility. Psychological determinants comprised the Depression Anxiety Stress Scale-21 (DASS-21) for emotional well-being, the Tampa Scale for Kinesiophobia (TSK) for kinesiophobia, and the Activities-Specific Balance Confidence (ABC) scale for balance confidence. Social determinants included educational attainment and the Short Form-36 (SF-36) for health-related quality of life. Results: Significant differences in biopsychosocial determinants were identified among the various pain intensity groups. Biological factors, including WOMAC scores, TUG, and 30STS tests; psychological factors, such as depression and anxiety (DASS-21) and kinesiophobia (TSK); and social factors, including mean years of education and all SF-36 subscales, were significantly worse in the severe pain group (p < 0.05). However, balance confidence did not differ between groups (p = 0.060). Patients in the severe pain group exhibited poorer outcomes across biological, psychological, and social domains, whereas the moderate pain group displayed worse biological and social outcomes when compared to the mild pain group (p < 0.05). Conclusion: This study emphasizes the significance of a biopsychosocial framework in managing pain in KOA patients. Worsened biological factors like knee function, mobility, and functional strength, alongside psychological issues such as depression and anxiety, influence pain intensity. Social determinants, including lower educational attainment and quality of life, highlight the need for patient-centered care. Future research should include diverse populations and longitudinal data to improve interventions and guide global health policies for integrating the biopsychosocial perspective for KOA management. © 2025 Elsevier B.V., All rights reserved.
Keywords: Biopsychosocial Model; Kinesiophobia; Knee Osteoarthritis; Pain; Physical Functional Performance; Quality Of Life; Ibm Spss 25 Software; Version 3.1.9.4 Of The G Power Program; Adult; Anxiety; Article; Biopsychosocial Model; Body Height; Body Mass; Body Weight; Charlson Comorbidity Index; Controlled Study; Cross-sectional Study; Depression; Depression, Anxiety And Stress Scale-21; Female; Human; Kinesiophobia; Knee Function; Knee Osteoarthritis; Likert Scale; Major Clinical Study; Male; Outcome Assessment; Pain Intensity; Quality Of Life; Short Form 36; Social Outcome; Sociodemographics; Tampa Scale For Kinesiophobia; Visual Analog Scale; Western Ontario And Mcmaster Universities Osteoarthritis Index; Aged; Arthralgia; Diagnosis; Etiology; Middle Aged; Pain Measurement; Pathophysiology; Psychology; Severity Of Illness Index; Aged; Arthralgia; Cross-sectional Studies; Female; Humans; Male; Middle Aged; Osteoarthritis, Knee; Pain Measurement; Quality Of Life; Severity Of Illness Index